Hippocampal structure, patterns of the calcium-binding proteins and neuron numbers in small echolocating bats - Maliković, Jovana; Schönbächler, Katja; Destro, Ana Luiza F.; Wolfer, David P.; Amrein, Irmgard (Frontiers in Neuroanatomy, 2025)
Even though bats are the second most speciose group of mammals, neuroanatomical studies of their hippocampus are rare, particularly of small echolocating bats. Here, we provide a qualitative and quantitative neuroanatomical analysis of the hippocampus of small echolocating bats (Phyllostomidae and Vespertilionidae). Calcium-binding proteins revealed species- and family-specific patterns for calbindin and calretinin. Interneuron staining for both proteins was very rare in phyllostomids, while calretinin marked subpopulations of CA3 pyramidal neurons in both families. Parvalbumin expression was consistent across bats and similar to other species. A unique calretinin-positive calbindin-negative zone was observed at the superficial boundary of the CA3 pyramidal cell layer in phyllostomid bats. This zone defined a gap between pyramidal cells and the zinc-positive mossy fibers. We hypothesize that this gap might either stem from calretinin-positive afferents displacing the zinc-positive mossy fiber boutons, or from a complete segregation of neurochemically distinct mossy boutons. Furthermore, we observed a distinct dorsoventral shift in the length of the upper and lower blade of the granule cell layer in all species. In terms of hippocampal neuron numbers, bats were characterized by a rather small granule cell and subicular neuron population, but a well-developed CA3. In a correspondence analysis, preferred diet segregated phyllostomids into a hilus-dominant omnivorous and frugivorous species group, and a subiculum-dominant group containing vampire bats and nectivorous species. Although the two families overlapped considerably, the cellular composition of the phyllostomid hippocampus can be described as output dominant, while in vespertilionids neuron populations on the hippocampal input side are more dominant. Neuroanatomical and ecological variability and unique traits within echolocating bats as shown here can provide a rich source for investigating structure-function relationships.